The Profitability Analysis of the Logistics Industry Companies in the Balkan Countries - Bojana Vuković; Sunčica Milutinović; Vera Mirović; Nikola Milićević (Promet (Zagreb), 2020)
The main purpose of this paper is to research the factors that have an impact on the company profitability in the logistics industry during a five-year period (2013-2017). The sample includes 748 active companies operating in the logistics industry in the Balkan countries. Bearing in mind that logistics is an essential instrument of competitiveness and profitability of the company operations and that logistics is one of the most profitable industries, this paper used the panel data model with fixed effect in order to analyse profitability. The obtained results showed that four out of the six studied variables (company size, tangibility of assets, liquidity, and asset turnover ratio) have a statistically significant impact on profitability. The results provide guidelines for increasing profitability and improving the performance of logistics companies, given that an efficient planning system, managing and controlling the logistics system are key determinants of profitable business operations.